Extremely low frequency electromagnetic fields impair the cognitive and motor abilities of honey bees - Lima, M. A. P.; Shepherd, S.; Oliveira, E. E.; Sharkh, S. M.; Jackson, C. W.; Newland, P. L. (Scientific Reports, 2018)
Extremely low frequency electromagnetic field (ELF EMF) pollution from overhead powerlines is known to cause biological effects across many phyla, but these effects are poorly understood. Honey bees are important pollinators across the globe and due to their foraging flights are exposed to relatively high levels of ELF EMF in proximity to powerlines. Here we ask how acute exposure to 50 Hz ELF EMFs at levels ranging from 20–100 μT, found at ground level below powerline conductors, to 1000–7000 μT, found within 1 m of the conductors, affects honey bee olfactory learning, flight, foraging activity and feeding. ELF EMF exposure was found to reduce learning, alter flight dynamics, reduce the success of foraging flights towards food sources, and feeding. The results suggest that 50 Hz ELF EMFs emitted from powerlines may represent a prominent environmental stressor for honey bees, with the potential to impact on their cognitive and motor abilities, which could in turn reduce their ability to pollinate crops.
Keywords: Electromagnetic fields; Bees